Exploring novel pyridine carboxamide derivatives as urease inhibitors: synthesis, molecular docking, kinetic studies and ADME profile - Ayesha Naseer; Faisal Abdulrhman Osra; Asia Naz Awan; Aqeel Imran; Abdul Hameed; Syed Adnan Ali Shah; Jamshed Iqbal; Zainul Amiruddin Zakaria (Multidisciplinary Digital Publishing Institute, 2022)
The rapid development of resistance by ureolytic bacteria which are involved in various life-threatening conditions such as gastric and duodenal cancer has induced the need to develop a new line of therapy which has anti-urease activity. A series of pyridine carboxamide and carbothioamide derivatives which also have some novel structures were synthesized via condensation reaction and investigated against urease for their inhibitory action. Among the series, 5-chloropyridine-2 yl-methylene hydrazine carbothioamide (Rx-6) and pyridine 2-yl-methylene hydrazine carboxamide (Rx-7) IC50 = 1.07 ± 0.043 µM, 2.18 ± 0.058 µM both possessed significant activity. Furthermore, molecular docking and kinetic studies were performed for the most potent inhibitors to demonstrate the binding mode of the active pyridine carbothioamide with the enzyme urease and its mode of interaction. The ADME profile also showed that all the synthesized molecules present oral bioavailability and high GI absorption.